Análise da influência de tratamento térmico na resistência à corrosão-erosão do aço inoxidável AISI 304 - Louzada, Dímisson Abreu (2008)
This work intends to evaluate the damaged caused by the erosion-corrosion process of a stainless steels AISI 304, under four microstructures conditions, used in various applications by the erosion, corrosion, and erosion-corrosion rates. With these rates it is possible to verify if there is a synergistic effect under the test conditions. For that reason, a slurry pot tester was useful. The experiments were performed at an impact of 7,5 m/s at room temperature. The abrasive particles of quartz used are in granulometric range 150 μm and an average sand concentration of 4 % wt. The corrosion and erosion-corrosion tests were performed in a solution of sodium chloride and acetic acid with 10-3 mol/l of sodium thiosulfate which is used to simulate the effect of the H2S presence. The samples obtained from dowel steel are cylindrical with 4,76 mm diameter and were weighted before and after each test. The erosion rate is in good agreement with the literature and is higher for solubility samples. The erosion rate is higher than the corrosion rate. The synergistic effect was observed for the test conditions.